2022
DOI: 10.1158/1078-0432.ccr-21-4554
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Adjuvant Nivolumab Following Salvage Resection in Patients with Recurrent Squamous Cell Carcinoma of the Head and Neck

Abstract: PURPOSE: Loco-regional relapse in patients with head and neck squamous cell carcinoma (HNSCC) is common, approaching 50% for some subsites despite multi-modality therapy. Salvage surgery is the standard of care, but able to achieve durable control in only a minority of patients. While adjuvant RT or chemo-RT is offered to select patients, this approach can be prohibitively toxic. Given the activity and tolerability of PD-1 inhibitors in metastatic HNSCC, we investigated the safety and efficacy of adjuvant nivo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the immunotherapy of head and neck cancer, it's reported that TMB was higher in responders compared with non-responders [35]. However, results from another ICI cohort containing 261 patients presented that TMB≥10 mut/Mb failed to predict both OS and disease-free survival [36]. Our present study demonstrated that the top 20% of TMB (≥9.51 mut/Mb) could predict OS in patients with ICI treatment, at which cutoff, TMB exhibited no predictive role for that without ICI therapy.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 98%
“…In the immunotherapy of head and neck cancer, it's reported that TMB was higher in responders compared with non-responders [35]. However, results from another ICI cohort containing 261 patients presented that TMB≥10 mut/Mb failed to predict both OS and disease-free survival [36]. Our present study demonstrated that the top 20% of TMB (≥9.51 mut/Mb) could predict OS in patients with ICI treatment, at which cutoff, TMB exhibited no predictive role for that without ICI therapy.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 98%
“…All 20 studies reported the incidences of any grade and grade three or more trAEs (Table 1). Nine studies were anti-PD1 monotherapy, [3][4][5][14][15][16][17][18][19] eight studies were anti-PDL1 monotherapy, 6,7,[20][21][22][23][24][25] seven studies were ICIs combination therapy, [6][7][8]14,20,26,27 five studies were median duration of treatment ≤3months, eight studies were >3 months, nine studies were RCT, and 11 studies were non-RCT. Seventeen studies reported the incidence of treatment-related deaths, among which eight studies were anti-PD1 monotherapy, eight studies were anti-PDL1 monotherapy, and six studies were ICIs combination therapy.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Adjuvant PD-1 blockade immunotherapy in combination with salvage surgery is being evaluated in multiple clinical trials as a means of improving the overall survival of patients with recurrent or metastatic HNSCC [100,101]. Surgery in this context functions as previously described by reducing tumor bulk and leaving a lesser amount of cancerous tissue for the immune system to combat.…”
Section: Salvage Surgerymentioning
confidence: 99%
“…The adjuvant PD-1 blockade in this context then promotes the removal of immunosuppressive barriers to immune response against residual cancer cells. A recent phase II clinical trial has shown a tolerable safety profile and improved disease-free survival compared to historical control samples at two-year follow-up [101].…”
Section: Salvage Surgerymentioning
confidence: 99%